Algeria : stabilization and transition to the market - Nashashibi, Karim A.; International Monetary Fund. (Washington, DC : International Monetary Fund, 1998)
This paper offers Algeria's recent experience with macroeconomic stabilization and systemic transformation from a centrally planned to a market economy. The analyses focuses on the period since 1994 when Algeria embarked on a comprehensive reform program that has benefitted from IMF support, first through a one-year Stand-by Arrangement, and from May 1995, through a three-year arrangement under the Extended Fund Facility.
Includes bibliographical references.
oif 27/04/15
Loan
Keywords: Mixed economy -- Algeria; Economic stabilization -- Algeria; Structural adjustment (Economic policy) -- Algeria; Algeria -- Economic conditions -- 1962-